Porosity of CHA zeolite driving the formation of polyaromatic coke species in the methanol to olefins reaction - Florindo, Bianca R. [UNESP]; Catuzo, Gabriel L. [UNESP]; Martins, Leandro [UNESP] (Sociedade Brasileira de Quimica (SBQ), 2021)
The pore size of the chabazite structure is exceptionally suitable for the methanol to olefins (MTO) reaction. The reaction has an induction period required for the formation of a hydrocarbon pool (HP), usually composed of aromatic compounds of different sizes. HP is alkylated by methanol and afterward cracked, leading to the formation of olefins. Despite the importance of HP, its formation and growth in size are exceedingly dependent on the porosity of the catalyst. The ideal is that the formed HP remains stable throughout the reaction because the growth in its size causes blockage of the small catalyst pores, decreasing its capacity. Herein we studied chabazite zeolites with different porosity and structure, caused by variation in the particle size and pores' volume. Porosity influenced the formation of HP species in quantity (as revealed by thermogravimetric analysis (TGA)) and polymerization degree (gas chromatography coupled with mass spectrometer (GC-MS) analysis) and, consequently, the MTO reaction's performance.
Keywords: CHA zeolite; Identification of coke; MTO reaction; Porosity of catalyst